Redescription of Deltamysis holmquistae Bowman & Orsi, 1992 (Crustacea: Mysida: Mysidae), a mysid species new to the Atlantic Ocean with observations on the taxonomic status of Kochimysis Panampunnayil & Biju, 2007 - Scripter, Matthew J.; Price, W. Wayne; Heard, Richard W. (Zootaxa, 2020)
The first occurrences of the estuarine mysid Deltamysis holmquistae Bowman & Orsi from the Atlantic Ocean are documented from sites on the eastern Florida and northwest Gulf of Mexico (Texas) coasts of North America. Based on examination of type material and specimens from Florida and Texas, considerable morphological variability and additional characters were observed necessitating a rediagnosis of the monotypic genus Deltamysis and a redescription of D. holmquistae. As a result of these new taxonomic criteria, the Indian Ocean species, Kochimysis pillaii Panampunnayil & Biju, described from southwest coastal India, is subsumed as a junior synonym of D. holmquistae. The current distribution of this apparently invasive species is probably due to maritime commerce. The geographical location of the endemic or source populations of D. holmquistae remains undetermined; however, its co-occurrence in California with three introduced Asian mysids suggests a northern Indian Ocean or northwest Pacific origin.